PENAMBAHAN RIMPANG KUNYIT (CURCUMA DOMESTICA VAL), RIMPANG TEMULAWAK (CURCUMA XANTHORRIZA ROXB) DAN RIMPANG TEMU PUTIH (CURCUMA ZEDOARIA ROSC) DALAM RANSUM KOMERSIAL TERHADAP PERFORMANS BURUNG PUYUH (Coturnix-coturnix japonica) - Kaselung, Patri Seila; Montong, M E.K; Sarayar, C L.K; Saerang, J L.P (Universitas Sam Ratulangi, 2014)
ABSTRACT ADDITION TURMERIC, GINGER RHIZOME AND WHITE RHIZOME OF COMMERCIAL RATION ON QUAILS’ PERFORMANCES. This study aims to determie the effectiveness of the addition of Turmeric powder (Curcuma domestica Val), Javanese ginger powder (Curcuma xanthorriza Roxb) and White turmeric powder (Curcuma zedoaria Rosc) in a commercial ration towardsthe performance of quail. The material used were 120 female quails 6 weeks of age. We used the Completely Randomized Design with 4 treatments and 5 replications. The treatments were applied as follows : R0 = basic ration without turmeric, Javanese ginger, and white turmeric powder, R1 = base + 2% ration turmeric powder, R2 = base + 2% ration Javanese ginger powder, R3 = base + 2% ration of Javanese ginger and white turmeric powder. The results showed that the addition of turmeric powder, Javanese ginger powder and white turmeric powder in the ration was not significantly different (P > 0.05) on the performance of quails (feed consumption, egg production and feed conversion). We conclude that the addition of turmeric powder, Javanese ginger powder, and white turmeric powder as much as 2% in commercial rations didn’t raise the feedconsumption, egg production, and surpresses the feed conversion. Keywords : Quail, Turmeric, Javanese Ginger, White Turmeric